Measuring the Impacts of Argentina’s Presidential Election Process in 2023 on the Stock Market Performance Using a Dynamic Event Study Methodology - Eduardo Enrique Sandoval Álamos; Claudio René Molina Mac-Kay; Erwin Octavio Taipe Aquino (Risks)
This study measured the individual and conjoint effects of Argentina’s primaries and first- and second-voting presidential election results, as well as their post-election comparative effects, on the stock market performance of its most relevant economic sectors. Within four different estimation methods, the state-space specification outperformed the rest. The findings suggest that investors can under/overreact compared to post-election sectors performance, the public services sector being the exception. Therefore, those investors who anticipated the election results by liquidating positions in companies in the materials sector and investing more in companies in the energy and other industrial sectors achieved a superior performance.